A conceptual framework for inclusive participation in communal land development: feminism perspective - Zulu, Hlengiwe Patronella; Lukhele, Themba Mfanafuthi; Sabela, Primrose Thandekile (Frontiers in Sustainable Cities, 2025)
Participatory community development is considered as one of the important mechanisms of governance in ensuring inclusive and people centered development in emerging economies around the world. Remarkably, community participation has been promoted because of the associated perceived benefits such as collective decision making, ownership of community projects and sustainability of community initiatives. Despite all these associated benefits, there is an increasing concern that, in practice, community participation in relation to land development initiatives turned to be biased against and be exclusive of women. Against this backdrop, the conceptual study explores the prospects for women increased and meaningful participation in land development initiatives amid the patriarchal structures and barriers characterizing most of the societies in developing countries. Through the proposed conceptual framework, this study argues that to achieve inclusive participation in land development initiatives in communities, the agendas of women empowerment should be accompanied with ecofeminism, social capital and social acceptability principles as drivers of the transformation into the manifestation of inclusive participatory in relation to land development. The proposed conceptual framework together with the recommendations thereof in this study shed new insight to understand that, unless policies and programs of women empowerment on land development are synchronized with ecofeminist, social acceptability and social capital values, the realization of inclusive participation in communal land development in emerging economies will remain impossible.